PENINGKATAN DAYA SAING DAN PANGSA PASAR DALAM BISNIS OTOMOTIF MELALUI BRAND DAN PERSONAL INVOLVEMENT - NUNO SUTRISNO; EMIR KHARISMAR (Jurnal Bisnis dan Akuntansi, 2021)
The purpose of this study was to determine the effect of Personal Involvement, Sensory Brand Experience, Brand Awareness and Brand Image on Brand Equity at PT. SGMW Motor Indonesia in DKI Jakarta. The research method used in this research is through a survey. The data analysis was done quantitatively and used a causal research design. The sampling method used in this study is to use Non-Probability Sampling with purposive sampling technique. All sample data obtained by distributing questionnaires totaled 121 respondents and will be processed using SPSS 25 software. The data analysis technique used in this study is multiple linear regression. The results of this study indicate that Personal Involvement, Sensory Brand Experience, Brand Awareness and Brand Image have an influence on Brand Equity. This research is expected to provide input or suggestions to automotive companies, especially PT. SGMW Motor Indonesia or Wuling Motor which is the object of this research, is to be able to increase its competitiveness and market share in the automotive industry in Indonesia.